Gaya Kepemimpinan Lurah Balaroa Di Kecamatan Palu Barat Kota Palu - Filo Leonardo Tinggogoy; Hermansyah Hermansyah; Nasrullah Nasrullah (Sekolah Tinggi Ilmu Administrasi (STIA) Pembangunan Palu, 2021)
This study is intended to determine the leadership style of the village head in Balaroa, Sub-District West Palu, Palu. This type of research is descriptive. The types of data used are primary data and secondary data with data collection techniques namely observation, in-depth interviews, and documentation. While the theory used in this research is using the theory of Harsey and Blancherd (in Harbani Pasolong 2008) the indicators are: Instruction, Consultation, Participation, and Delegation. While the informants involved in this study were 5 people, four village apparatus and one community member. Based on the results of the research obtained by the author in the field, that the Leadership Style of the Lurah in Balaroa, Sub-District West Palu can be categorized as good, but the village apparatus has not been able to carry out their duties optimally in accordance with the leadership style of the Lurah, indicators that need to be a concern to be able to realize this style. The expected leadership for the apparatus is the Delegation aspect and the Control aspect, it is hoped that in the future the apparatus can carry out directions and tasks according to the leadership style that the Lurah has applied to his apparatus.